Pemetaan Kesenjangan Ekonomi: Analisis Data Panel dari 34 Provinsi di Indonesia - Feny Marissa; Hamira Hamira; Dwi Darma Puspita Sari; Deassy Apriani (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Income inequality remains a complex challenge in developing countries, including Indonesia. While it cannot be eliminated, it can be reduced to socially acceptable levels to maintain harmony in the system. This study analyzes the effect of the Human Development Index (HDI), poverty, economic growth, Regional Original Revenue (PAD), and Farmer Exchange Rate (NTP) on income inequality in Indonesia during 2000-2021. Using the panel data regression analysis technique with the Fixed Effects Model, the results show that economic growth and NTP significantly negatively affect inequality, helping to reduce it. In contrast, HDI and poverty increase inequality, while PAD has no significant effect. The intercept indicates that East Java, Central Java, and West Java have lower inequality, mainly due to the presence of growth centers and industries. This study suggests the development of new economic centers in poor regions as an effective strategy to reduce inequality in Indonesia.